Effect of stocking density on the productivity and profitability of the freshwater prawn Macrobrachium rosenbergii in the fattening phase in ponds, Costa Rica - Valverde, José (2020)
The aim of this study was to determine the productivity and profitability of fattening freshwater prawns cultivated in two stocking densities in ponds, applying a simple and appropriate technology for the transfer of knowledge to producers. The study was carried out in 2019 on a farm in the province of Limón, Costa Rica. The fattening stage was carried out using densities of 2.5 and 6.0 shrimp/m2. The productions obtained were 758.9 and 961.2 kg/ha, respectively (p<0.01). Assuming 2.7 cycles per year, the potential productivity would be 2049 and 2595 kg/ha/year, respectively. Variable production costs were higher at 6.0/m2 than at 2.5/m2 due to the increase in the purchase of more seeds and feeds. The cost of the seed represented 69% of the total investment in low stocking density and 77% in the highest. Farm sales revenue was higher at 6.0/m2 than at 2.5/m2. However, the most profitable stocking density was 2.5/m2 because even with lower production, it showed a higher profit. Gross profits were higher in the lowest stocking density, and there was no profitability in the highest, due not only to the higher proportion of prawns with commercial size in the first stock, but also to the increase in the cost of production in the second, where the seed represented the greatest expense. The economic sensitivity study suggests the use of the seeding density of 2.5/m2 has higher profitability, an attractive IRR (48.6%), relatively less time to recover the investment (2.1 years), a positive NPV and a cost benefit ratio. 2.0 which means that for every dollar invested US$2.0 was generated.